THE UTILIZATION OF READING ROOM AT ENGINEERING FACULTY OF PADANG STATE UNIVERSITY - 1817-1833 , Mita Dwi Putri (CIVED, 2016)
ABSTRACTThis research is aim to show the utilization of reading room at Civil and Electrical Engineering, Engineering Faculty of Padang State University with the  Civil an Electrical Engineering students, Engineering Faculty of Padang State University batch 2012 as the population.This research is a descriptive quantitative research with a population of 169 students and sample taking as the method, using Proportional Random Sampling as 199 respondents, consists of 49 respondests represent Civil Engineering Major and 70 respondents represent Electrical Engineering Major. Data was collected using questioneere with Likert Scale that consists of 4 choices of answer. The item amount in the quetioneereare 36 questions.The result of the research point out that the utilization of the reading room shows: (1) The supply of information in the departement reading room with percentage 41,18% is in a high category. (2) The right time to visit the departement reading room with percentage 42,02% iis in a high category. (3) The pleasing situation in the reading room with the percentage as 43,70% is in an average category. (4) The attitude and behavior of the employee in the departement reading room with the percentage  43,70% is in a high category. (5) The rules and order in the reading room with the percentage 44,54% is in a high category. Based on those results, it can be concluded that the department reading room is used perfectly by the students of Civil and Electrical Engineering Major. Keywords: Library, Reading Room, Engineering Faculty